The Role of Wonder in Students’ Conception of and Learning About Evolution - Bodil Sundberg; Magdalena Andersson (Center for Educational Policy Studies Journal)
Learning about evolution can be challenging for students, as a full understanding may require them to see the world in new ways, to master a disciplinary language and to understand complex processes. Drawing on a long line of theoretically grounded arguments of philosophers and researchers for including wonder in science teaching, we report on the results of an empirical study with the primary aim of investigating the role of wonder in students’ learning about evolution. The study was carried out through a formative intervention in which two researchers in science education collaborated with a seventh-grade teacher. Over a period of six weeks, 45 students participated in lessons and workshops aimed at eliciting a sense of wonder in relation to concepts that are known to impact the learning of evolution. We incorporated four ‘triggers’ to elicit students’ wonder in the science class: aesthetic experiences, defiance of expectations, agency and awareness of a mystery within the ordinary. Logbook entries and interviews with student pairs provided empirical material for a qualitative analysis of the role of wonder in the students’ meaning-making about, learning of and engagement in evolution. The results show that it is possible to design science teaching that triggers students’ wonder in relation to an intended learning object. The results also reveal that the participating students described their sense of wonder in qualitatively different ways and that they still struggled to make sense of the concept of evolution after six weeks of teaching.